The Effect of Oxygen Gas Flow Rate on TiO2 Thin Film Prepared by Double Zone CVD Technique - Mohd Haron, Nurul Amira; Lias, Jais (Evolution in Electrical and Electronic Engineering, 2020)
The research was conducted to determine the deposited TiO2 thin film of titanium dioxide on a 210º C and 60º C glass substratum using a double zone Chemical Vapor Deposition (CVD) furnace. Through a different oxygen gas, the flow rate was varied in range of 0.6 ml ~ 1.2 ml. The effect of oxygen gas flow rate thin films was routinely tested at room temperature on titanium dioxide TiO2 and will be annealed at a fixed time, which is 1 hour at 500º C. The crystal structure properties on TiO2 was obtained using X-Ray Diffraction (XRD). In addition, the studies of surface morphology was performed using Atomic Force Microscope (AFM) and Field Effect Scanning Electron Microscopy (FE-SEM). The TiO2 electrical properties were evaluated to obtain its resistivity and conductivity using a four-point probe. The characterization of TiO2 thin film conducted more systematically and discussed in these research studies.